Fecal Immunoglobulin A Antibodies in Dogs Infected or Vaccinated with Canine Coronavirus - Decaro, Nicola (American Society for Microbiology, 2004)
Fecal secretory immunoglobulin A (IgA) antibodies in dogs infected or vaccinated with canine coronavirus (CCV) were evaluated by an enzyme-linked immunosorbent assay. The study was carried out with 32 fecal samples collected just before inoculation and at 28 days postinoculation. Five groups were studied: naturally infected dogs, experimentally infected dogs, dogs inoculated with a modified live (ML) CCV vaccine by the intramuscular route, dogs inoculated with an ML CCV vaccine by the oronasal route, and dogs given an inactivated CCV vaccine. Both the naturally and the experimentally infected dogs developed high levels of fecal IgAs. Interestingly, dogs inoculated with the ML CCV vaccine by the oronasal route developed levels of fecal IgA that were higher than those observed in the dogs inoculated with the same CCV vaccine by the intramuscular route or those observed in dogs inoculated with the inactivated vaccine. A relationship between the level of fecal IgAs to CCV and the degree of protection against CCV infection was observed.